2012
DOI: 10.2174/156802612799362922
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Protein Kinases in the Malaria Parasite: Update of an Antimalarial Drug Target

Abstract: Millions of deaths each year are attributed to malaria worldwide. Transmitted through the bite of an Anopheles mosquito, infection and subsequent death from the Plasmodium species, most notably P. falciparum, can readily spread through a susceptible population. A malaria vaccine does not exist and resistance to virtually every antimalarial drug predicts that mortality and morbidity associated with this disease will increase. With only a few antimalarial drugs currently in the pipeline, new therapeutic options … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Indeed, in contrast to the traditional one drug – one target drug discovery paradigm, drug polypharmacology has gained a lot of attention in recent years [29]–[32]. For the particular case of malaria, small molecules acting with biologically relevant affinity on multiple P. falciparum targets represent an interesting strategy to retain therapeutic efficacy against the potential emergence of parasite resistance on individual targets, a concept already proposed for antimalarial protein kinase inhibitors [33], [34]. This is also supported by the observation that parasites show relatively slow resistance development against artemisinin, a drug that is believed to act on multiple targets [2].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in contrast to the traditional one drug – one target drug discovery paradigm, drug polypharmacology has gained a lot of attention in recent years [29]–[32]. For the particular case of malaria, small molecules acting with biologically relevant affinity on multiple P. falciparum targets represent an interesting strategy to retain therapeutic efficacy against the potential emergence of parasite resistance on individual targets, a concept already proposed for antimalarial protein kinase inhibitors [33], [34]. This is also supported by the observation that parasites show relatively slow resistance development against artemisinin, a drug that is believed to act on multiple targets [2].…”
Section: Discussionmentioning
confidence: 99%
“…Lestaurtinib (CEP-701) is a protein kinase inhibitor in development by Cephalon Inc for acute myelogenous leukaemia and myeloproliferative disorders. Clinical information on this compound was limited at the time of the study and protein kinase inhibitors have been suggested as an important target in malaria [9,40,41]. Thus, only lestaurtinib was progressed to the P. falciparum HuSCID mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds were of particular interest as they are essential throughout all stages of the Plasmodium spp. lifecycle [40,41]. Many protein kinase inhibitors have been registered or investigated, primarily for the treatment of cancer, although these drugs have known toxicities that have discouraged their use in malaria.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is made possible by the differences between parasite and host PK homologs [76]. Zhang et al [77] reviewed the applications and the progress made in the targeting of specific PKs as antimalarial drugs against Plasmodium parasites. Proof of principle of this approach has been demonstrated by the inhibition of human PKs using chemical ligands to treat cancers and other diseases [78,79].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%